Curation and expansion of the Human Phenotype Ontology for systemic autoinflammatory diseases improves phenotype-driven disease-matching - Maassen, Willem; Legger, Geertje; Kul Cinar, Ovgu; van Daele, Paul; Gattorno, Marco; Bader-Meunier, Brigitte; Wouters, Carine; Briggs, Tracy; Johansson, Lennart; van der Velde, Joeri; Swertz, Morris; Omoyinmi, Ebun; et al. (Frontiers in Immunology, 2023)
Accurate and standardised phenotypic descriptions are essential in diagnosing rare diseases and discovering new diseases, and the Human Phenotype Ontology (HPO) system was developed to provide a rich collection of hierarchical phenotypic descriptions. However, although the HPO terms for inborn errors of immunity have been improved and curated, it has not been investigated whether this curation improves the diagnosis of systemic auto inflammatory disease (SAID) patients. Here, we aimed to study if improved HPO annotation for SAIDs enhanced SAID identification and to demonstrate the potential of phenotype-driven genome diagnostics using curated HPO terms for SAIDs. We collected HPO terms from 98 genetically confirmed SAID patients across eight different European SAID expertise centres and used the LIRICAL computational algorithm to estimate the effect of HPO curation on the prioritisation of the correct SAID for each patient. Our results show that the percentage of correct diagnoses increased from 66% to 86% and that the number of diagnoses with the highest ranking increased from 38 to 45. In a further pilot study, curation also improved HPO-based WES analysis, diagnosing 10/12 patients before and 12/12 after curation. In addition, the average number of candidate diseases that needed to be interpreted in the analysis decreased from 35 to 2. This study demonstrates that curation of HPO terms can increase identification of the correct diagnosis, emphasising the high potential of HPO-based genome diagnostics for SAIDs.